Neurosociology: Fundamentals and Current Findings - Franks, David D.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2019)
This book offers an introduction to the fundamentals of neurosociology and presents the newest issues and findings in the field. It describes the evolution of the brain and its social nature. It examines the concept of knowing and what can be known, as well as the subjective sensations we experience. Next, it explores the ubiquitousness of New Unconsciousness and the latest conclusions about mirror neurons. Additional themes and concepts described are sex differences in the brain, imitation, determinism and agency. The book brings together neuroscience and sociology, two fields that are very different in terms of method, theory, tradition and practice. It does so building on the following premise: If our brains have been forged evolutionarily over the many centuries for social life, sociologists should have the opportunity, if not the duty, to know about it whatever the reservations of some who think that any approach that includes biology must be reductionistic.
Chapter 1. Introduction -- Chapter 2. The Evolution of the Human Brain -- Chapter 3. What is Social about the Human Brain? -- Chapter 4. Knower and the Known -- Chapter 5. Consciousness, Qualia, and Subjective Experience -- Chapter 6. The Post-Freudian Unconscious: Agency and Awareness -- Chapter 7. Mirror Neurons, a Return to Pragmatism and Implications for an Embodied Intersubjectivity -- Chapter 8. Sex Differences in the Human Brain -- Chapter 9. Imitation in Social Life and its Anatomical Brain Supports -- Chapter 10. Determinism and Agency -- Chapter 11. Summary and Conclusions -- .
Keywords: Sociology; Neuropsychology; Neurology .; Neurosciences; Sociology; Neuropsychology; Neurology; Neuroscience